A vulnerability inspired Universal Design of Justice - Sarrett, Jennifer C (Punishment & society, 2022)
The US criminal justice system is built on the notion of the liberal, autonomous subject who chooses to engage in criminal activity, rather than one that addresses the underlying factors that lead to crime. I argue that by combining Vulnerability Theory, a feminist legal theory focused on universal human vulnerability, and Universal Design, a disability approach aimed at creating access for the widest range of bodies and minds, we can create a system that necessitates an analysis of how social institutions are related to risk for criminal justice involvement to reduce the harms perpetuated by criminal justice involvement. Applied to criminal justice reform together, I develop a Vulnerability Inspired Universal Design of Justice that identifies important areas of reform throughout our social institutions in order to reduce the harms of the criminal justice system.